2016
DOI: 10.1097/iae.0000000000001069
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Hole–associated Epiretinal Proliferation

Abstract: Lamellar macular hole with LHEP may demonstrate closure after pars plana vitrectomy with LHEP and internal limiting membrane peeling and gas tamponade. There was considerable improvement in visual acuity. It is possible that LHEP originates from middle retinal layers of the lamellar hole defect because it contains retinal glial cells, specifically Müller cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 8 publications
5
64
1
Order By: Relevance
“…Thus, it is thought that the LHEP may be a response to hole formation rather than a cause-that is, the LHEP is not thought to exert traction contributing to hole formation. [14][15][16] Consistent with this hypothesis, the LHEP identified in this study was found in association with an eccentric macular hole in an area of retinitis that presumably occurred secondary to atrophy from CMV retinitis rather LHEPinduced traction.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, it is thought that the LHEP may be a response to hole formation rather than a cause-that is, the LHEP is not thought to exert traction contributing to hole formation. [14][15][16] Consistent with this hypothesis, the LHEP identified in this study was found in association with an eccentric macular hole in an area of retinitis that presumably occurred secondary to atrophy from CMV retinitis rather LHEPinduced traction.…”
Section: Discussionsupporting
confidence: 84%
“…Our histological analysis was preliminary, and we cannot definitively conclude that LHEP originates either from the retina 5,10 or from the vitreous. 3,4 Our present RRM results also cannot show that carotenoid-specific signals come from the Müller cells.…”
Section: Discussionmentioning
confidence: 87%
“…Pang et al 10 demonstrated histologically that LHEP was composed of proliferated Müller cells and argued that LHEP originates from the retina. 5 The GFAP-positive immunostaining of LHEP in the present study corroborated their findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations